Variables, kinetics, and thermodynamics analysis of 6-gingerol recovery from Bentong ginger using supercritical Carbon dioxide - Kamaruddin, Muhammad Syafiq Hakimi (2024)
Bentong ginger is recognised for its notable concentrations of advantageous constituents, specifically 6-gingerol, which have been associated with several bioactive qualities including antioxidant, anticancer, anti-inflammatory, antibacterial, and antibiofilm actions. The presence of a β-hydroxy keto functional group in the structure of 6-gingerol makes them thermally labile and undergo facile dehydration at high temperatures. Traditionally, bioactive compounds were extracted from plant materials using conventional techniques such as Soxhlet extraction. However, conventional extraction is known for its various shortcomings, such as high solvent consumption, longer extraction time, and critically, high-temperature processing, which can cause dehydration of 6-gingerol compounds in this study. Alternatively, this study uses green extraction, supercritical carbon dioxide (scCO2) which feature mild temperatures, short extraction times and minimal organic solvents. This study aims to evaluate the effect of scCO2 process variables and material process condition, namely pressure, temperature, and particle size, on the 6-gingerol recovery and to determine its optimal processing conditions. In addition, three empirical kinetic models, the Peleg, first-order, and two-site kinetic models were analyzed to study the mechanism of 6-gingerol extraction from Bentong ginger using scCO2. A Central Composite Design (CCD) was employed to investigate and optimize process conditions of pressures (10-30 MPa), temperatures (40-60°C), and particle sizes ranging (300-600 μm) at a fixed CO2 flow rate of 15 g/m for a 120 minutes extraction time. Pressure had the most positive effect on the extraction of 6-gingerol, followed by temperature and particle size. The optimum conditions were estimated at 25 MPa, 40°C, and 300 μm, respectively, with the highest 6-gingerol content (171.26 mg/g), total phenolic content (17.84 GAE mg/g), total flavonoid content (74.46 QE mg/g), and radical scavenging activity (91.14%). The good fit between all empirical models and the experimental data under all investigated conditions with a high R2 (> 0.95) shows the fitness of all models employed to described the behaviour of 6-gingerol extraction. However, the two-site kinetic model provided the most accurate description of experimental results, with the lowest range of RMSE (7.436-27.173) and strengthens by chi-square (χ2) compared to first-order and Peleg's models. The data exhibited a linear correlation, as predicted by the Arrhenius equation, with an activation energy (Ea) of 10.290 kJ/mol-1 and a pre-exponential factor of 91.37 s-1. Finally, the thermodynamic parameters, namely Gibbs' free energy (ΔG) (-0.494 kJ/mol-1), enthalpy change (ΔH) (-19.955 kJ/mol-1), and entropy change (ΔS) (0.062 J/mol-1), were determined at the optimal temperature of the extraction process. This study demonstrates that scCO2 extraction is a highly effective and environmentally friendly method for obtaining 6-gingerol from Bentong ginger, optimizing bioactive compound recovery while minimizing thermal degradation. The identified optimal conditions and the robust fit of the kinetic models confirm the efficiency and predictability of this extraction method. The thermodynamic analysis findings not only advance the understanding of green extraction technologies but also underscore their potential application in enhancing the yield and quality of bioactive compounds from natural sources.